Detecção da infecção subclínica de Mycobacterium leprae em menores de quinze anos, contactantes de hansenianos, Fortaleza - Ceará - Lourenço, Delaide Sampaio Dias (2016)
Leprosy is an infectious disease caused by Mycobacterium leprae, obligate intracellular bacillus. Due to the increase in the incidence of new cases in juveniles under 15 years and the debilitating potential of the disease, especially in paucibacillary patients and neural forms, it is necessary to use detection tools of the presence of the bacillus, in order to diagnose the onset of the disease or subclinical infection detection contacts of cases. This study aimed to investigate the possibility of subclinical infection in contacts ≥5 and <15 years of new cases, detected in Dona Libania Dermatology Centre, in Fortaleza-Ceara. Participated in this study, 69 index cases and 101 contacts under 15 years. Until now, no study sought subclinical detection of contacts of new leprosy cases treated at a Reference Unit. The collected material was analyzed using three techniques: determination of bacterial index, according to the Procedural Guidelines of Bacilloscopy Technical Leprosy of the Ministry of Health-2010; molecular detection of M. leprae DNA in nasal secretion, collected with pre-humidified swabs in Tris-EDTA buffer. The DNA extraction was performed using the DNeasy Blood and Tissue Kit Qiagen, held at -20°C, for subsequent amplification. The RLEP-R1 e RLEP-R2 primers were used for the specific region RLEP. The PCR reaction occurred in a thermocycler using the kit Ilustra™ Pure Taq Ready-to-go PCR beads GE HEALTHCARE; ML-Flow analysis, immunoassay for the detection of IgM PGL-1, which was adopted collection technique of whole blood, making up a puncture on the right or left forefinger. Measuring the positivity of the three techniques used in the study, we obtained the frequencies of 16.1% for PCR DNA, 1.98% for bacterial index in nasal secretion and 33.7% for ML-Flow. The M. leprae DNA PCR combined with serology of anti-PGL-1 antibodies show how sensitive and specific tools, which can assist in monitoring contacts at greater risk of developing the disease, especially in childhood. The detection of M. leprae in the nasal mucosa reflects the presence of this site bacillus, which can become a source of infection or transmission. This information combined with the investigation of seropositivity anti-PGL-1 strengthen the diagnosis of subclinical infection, including the possibility of the presence of bacillus in other sites, for example, skin and/or nerves.